Reproductive Health Care for HIV+ Young Women: What Should We Do? - Raymond Surya; Harry Prawiro Tantry; Dwiana Ocviyanti (PT. Kalbe Farma Tbk., 2022)
Introduction: This article aims to discuss reproductive health for young woman with positive HIV during postnatal care. Discussion: In HIV positive patients, ART treatment protocols may vary. Hormonal contraception in the form of combined oral contraception (COC), progestin-only pill, depo medroxyprogesteron acetate (DMPA), and implant are considered safe. Intrauterine device (IUD) is also safe for positive HIV women. Cervical cancer screening with Pap smear is performed at the initial diagnosis of HIV in patient less than 30 years of age. Summary: Antiretroviral therapy should be initiated early. HIV patients can safely use either hormonal contraception or IUD. Cervical cancer screening should be performed at the initial diagnosis of HIV.Pendahuluan: Artikel ini mendiskusikan kesehatan reproduksi wanita muda HIV positif selama perawatan pascamelahirkan. Diskusi: Pada pasien positif HIV, protokol terapi antiretrovirus cukup bervariasi. Kontrasepsi hormonal dalam bentuk pil oral kombinasi (POK), pil berbasis progestin, depo medroksiprogesteron asetat (DMPA), dan implan aman untuk pasien HIV positif. Skrining kanker serviks dengan Pap smear sebaiknya dilakukan saat awal terdiagnosis HIV pada pasien usia <30 tahun. Simpulan: Terapi antiretrovirus sebaiknya dimulai sedini mungkin. Pasien HIV aman menggunakan kontrasepsi hormonal maupun spiral. Skrining kanker serviks sebaiknya dilakukan saat awal terdiagnosis HIV.